The principles of creation and application of computer simulators in the tasks of electric power industry - Zachepa, Iurii; Zachepa, Nataliia; Ganzevich, Ivan; Shokarov, Dmytro; Cherkashyna, Halina (Національний технічний університет "Харківський політехнічний інститут", 2022)
The work presents the structure and the necessary complex of elements that ensure the functioning of computer simulators-simulators in the tasks of electric power engineering. The organization of the system for ensuring work in the given computer simulator-simulator is proposed. On the basis of the formulated general technical requirements for simulator software, their tasks and functions, a computer simulator-simulator of an autonomous power-generating installation was developed to practice the skills of technical operation of electrical installations of consumers. Mathematical support for the formation of subprograms as independent elements capable of interacting with each other is proposed. On the basis of the formulated general technical requirements for the software of the simulator, its tasks and functions, a computer simulator of an autonomous power plant was created to form the skills of technical operation of the consumer of electrical equipment. An algorithm for software and hardware implementation of a computer simulator-simulator, identical to a real physical autonomous minipower plant based on a diesel-generator unit, has been developed.

В роботі представлено структуру та необхідний комплекс елементів, що забезпечують функціонування комп'ютерних тренажерів-імітаторів в задачах електроенергетики. Запропоновано організацію системи забезпечення роботи в наведеному комп'ютерному тренажер-імітаторі. На основі сформульованих загальнотехнічних вимог, що висуваються до тренажерних програмних засобів, їх задач і функцій, для відпрацювання навичок технічної експлуатації електроустановок споживачів розроблено комп'ютерний тренажер-імітатор автономної енергогенеруючої установки. Запропоновано математичне забезпечення формуванні підпрограм як самостійних елементів, здатних взаємодіяти між собою. На основі сформульованих загальних технічних вимог до програмного забезпечення тренажера, його завдань і функцій створено комп’ютерний тренажер автономної електростанції для формування навичок технічної експлуатації споживача електроустаткування. Розроблено алгоритм програмно-апаратної реалізації комп'ютерного тренажера-імітатора, тотожного реальній фізичній автономній мініелектростанції на базі дизель-генераторної установки.
Принципи створення та застосування комп'ютерних тренажерів-імітаторів в задачах електроенергетики
Keywords: virtual laboratory complexes; computer simulator; distance learning; automated learning systems; віртуальні лабораторні комплекси; комп'ютерний тренажер-імітатор; дистанційне навчання; автоматизовані навчальні системи